2016
DOI: 10.1177/1948550616646424
|View full text |Cite
|
Sign up to set email alerts
|

Do Psychologically Adjusted Individuals Know What Other People Really Think About Them? The Link Between Psychological Adjustment and Meta-Accuracy

Abstract: Do psychologically adjusted individuals know what other people think about them? Participants rated their own personality and levels of intrapersonal and interpersonal adjustment and also estimated how a new acquaintance and friends perceived them on core personality traits. These individuals rated the participant's personality and friends described participants' adjustment. Intrapersonally and interpersonally adjusted individuals were aware of the positive rather than the distinctive and potentially negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 43 publications
(55 reference statements)
4
51
0
Order By: Relevance
“…However, the Blissfully Blind Hypothesis predicts that people with interpersonal problems have weaker meta‐insight, or are less able to make valid distinctions between self‐views and others’ perceptions. Indeed, the same study showing that interpersonal adjustment was linked to distinctive meta‐accuracy showed that adjusted individuals had higher meta‐insight as well (Carlson, ). Thus, Meg's problems might persist because she fails to realize the ways in which Jon experiences her differently from how she experiences herself.…”
Section: Interpersonal Problemsmentioning
confidence: 96%
See 4 more Smart Citations
“…However, the Blissfully Blind Hypothesis predicts that people with interpersonal problems have weaker meta‐insight, or are less able to make valid distinctions between self‐views and others’ perceptions. Indeed, the same study showing that interpersonal adjustment was linked to distinctive meta‐accuracy showed that adjusted individuals had higher meta‐insight as well (Carlson, ). Thus, Meg's problems might persist because she fails to realize the ways in which Jon experiences her differently from how she experiences herself.…”
Section: Interpersonal Problemsmentioning
confidence: 96%
“…Indeed, poor awareness might partially explain why people with interpersonal problems behave in maladaptive ways, but the content of their metaperceptions might also partially explain their maladaptive patterns of behavior. The degree to which people expect to be seen in desirable ways, or the extent to which they feel valued, as well as the degree to which people think others see them as they see themselves, or the extent to which they feel understood, are important components of relationship quality and well‐being (Campbell, Lackenbauer, & Muise, ; Carlson, , ; Murray, Holmes, MacDonald, & Ellsworth, ). People with interpersonal problems might feel less valued or understood, and this negative subjective reality might exacerbate and maintain their problems.…”
Section: Interpersonal Problemsmentioning
confidence: 99%
See 3 more Smart Citations